Auckland, New Zealand – fair game for central party politics. Issue 4 (4th July 2019) - Webster, Karen; Asquith, Andy; Rohan, Maheswaren; Cardow, Andrew; Majavu, Mandisi
ABSTRACT: This paper explores the influence of central party politics in Auckland local government, in New Zealand's largest city, following the 2010 amalgamation. Political parties have been an accepted and dominant presence in European representative democratic local government, throughout the 20 th century. Not so, however, in New Zealand and Australia, where citizens have 'flocked to the banner "Keep Politics out of Local Government". Our analysis of the self-declared party accreditation status of candidates and elected members demonstrates that political affiliation, at least in the main centre Auckland, is on the rise, counter to assumptions that New Zealand local government is largely removed from central politics.